2017
DOI: 10.1016/j.drugalcdep.2016.12.010
|View full text |Cite|
|
Sign up to set email alerts
|

Subjective experiences at first use of cigarette, e-cigarettes, hookah, and cigar products among Texas adolescents

Abstract: Introduction Subjective experiences (“SEs”) at first cigarette use have been thoroughly examined; however, limited research has examined SEs at first use of non-cigarette products. This study addresses this gap in the literature. Methods Cross-sectional data from 6th, 8th and 10th grade students in four metropolitan areas of Texas (n = 3907/N = 461,069). Nausea, coughing, relaxation, rush/buzz, and dizziness at first use were assessed for cigarettes, e-cigarettes, hookah, and cigar products. Chi-square analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…E-cigarettes appear to be less off-putting than conventional cigarettes, which may contribute to their growing popularity among adolescents. Adolescents in two U.S. cities reported experiencing fewer negative symptoms from e-cigarettes than conventional cigarettes in our small pilot study, findings that are consistent with previous studies of a national sample of adults [ 7 ] and of adolescents in Texas [ 8 ]. A novelty of our study is the use of open-ended questions, in which adolescents made unprompted comments about experiencing fewer negative symptoms from e-cigarettes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…E-cigarettes appear to be less off-putting than conventional cigarettes, which may contribute to their growing popularity among adolescents. Adolescents in two U.S. cities reported experiencing fewer negative symptoms from e-cigarettes than conventional cigarettes in our small pilot study, findings that are consistent with previous studies of a national sample of adults [ 7 ] and of adolescents in Texas [ 8 ]. A novelty of our study is the use of open-ended questions, in which adolescents made unprompted comments about experiencing fewer negative symptoms from e-cigarettes.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, symptoms experienced at first e-cigarette use were not associated with current e-cigarette use. In the only other study to examine the influence of adolescents’ first experiences with e-cigarettes on current use, Mantey et al also found that positive and negative initial experiences at first use had no effect on past 30-day e-cigarette use [ 8 ]. Together, these findings suggest that the mechanisms leading to regular use of e-cigarettes and cigarettes among adolescents may have important differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although risk factors for experimenting with e-cigs and cigarettes may be similar, a small telephone survey of high-risk adolescents by Chen et al agrees that initial experiences are not [ 27 ]. In findings consistent with a large printed survey of unselected 6th through 10th grade students [ 28 ], cigarettes had more negative effects and were less calming than e-cigs, but delivered a better “buzz”. The studies also agree that adolescents’ positive and negative experiences with cigarettes were associated with increased and decreased odds of smoking, respectively, but initial experiences with e-cigs had no association with subsequent use.…”
Section: The Special Issuesupporting
confidence: 77%
“…As all emerging tobacco products bear their own health risks and offer additional possibilities for dual/poly use, it is critical to monitor rural trends in the use of these emerging products. Yet most research on emerging tobacco products has either looked at overall, national trends, 15–18 or focused on heavily populated areas, 1921 with very little focus on rural use of emerging tobacco products. Likewise, although there are extremely high rates of both cigarette and smokeless tobacco use among rural populations (e.g., one study on daily tobacco users in Appalachia found that one-third of the male participants used smokeless tobacco 22 ), research has paid little attention to rural individuals engaged in the dual- or poly-use of tobacco products.…”
Section: Introductionmentioning
confidence: 99%